Perancangan Sistem Informasi Cuti Karyawan Berbasis Web Pada PT Minda Asean Automotive - Erlin Nur Safita (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2024)
This leave problem occurs because the system applied is still manual and not computerized. The problem with submitting employee leave causes many parties to feel a lack of information such as how much data the amount of their remaining leave is, the approval process for submitting must first meet their respective superiors. Seeing the problems regarding employee leave, a website-based application is needed in the form of an information sistem for submitting employee leave that is able to provide information about employee leave, information on employee leave remaining and also submitting employee leave online